2020
DOI: 10.1016/j.neubiorev.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Implicit processing during inattentional blindness: A systematic review and meta-analysis

Abstract: We have no known conflict of interest to disclose. This research was funded by a grant from the Brazilian Coordination for the Improvement of Higher Education Personnel to APN and by a long-term structural grant from the Flemish Government (METH/14/02) to JW. The funding sources had no involvement in the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 123 publications
(245 reference statements)
0
13
0
1
Order By: Relevance
“…Load theory faces the challenge of rectifying this pattern of findings and future efforts ought to seek to clarify how attentional settings can afford processing benefits despite load under conditions of IB. For the neuroscientist, these findings may help in better understanding the nature of conscious processing-namely, that inhibition likely contributes to IB (Wood & Simons, 2017b) and that unexpected objects can be preferentially boosted into conscious awareness based purely on their semantic properties , both imply a considerable depth of "unconscious" processing must occur under conditions of IB-a similar conclusion to that reached by both Kreitz et al (2020) and Nobre et al (2020). The next question, then, is where or when within the visual processing cortical hierarchy does this unconscious processing bottleneck cease?…”
Section: Implications Recommendations and Conclusionmentioning
confidence: 72%
See 2 more Smart Citations
“…Load theory faces the challenge of rectifying this pattern of findings and future efforts ought to seek to clarify how attentional settings can afford processing benefits despite load under conditions of IB. For the neuroscientist, these findings may help in better understanding the nature of conscious processing-namely, that inhibition likely contributes to IB (Wood & Simons, 2017b) and that unexpected objects can be preferentially boosted into conscious awareness based purely on their semantic properties , both imply a considerable depth of "unconscious" processing must occur under conditions of IB-a similar conclusion to that reached by both Kreitz et al (2020) and Nobre et al (2020). The next question, then, is where or when within the visual processing cortical hierarchy does this unconscious processing bottleneck cease?…”
Section: Implications Recommendations and Conclusionmentioning
confidence: 72%
“…The former pooled data from their lab's prior studies and reported that correct guessing was above chance in observers who were, in their original analysis, considered inattentionally blind or deaf (Kreitz et al, 2020). Nobre et al (2020) reached a similar conclusion in their meta-analysis that focused on implicit processing during IB. Gibbs et al (2016) presented a systematic review of 13 studies examining the related phenomenon change blindness.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The list of methods and approaches validating the claim that contents can be processed and represented unconsciously could be extended further. For example, there is also the effect of implicit processing of unexpected stimuli left out of awareness due to “inattentional blindness” (reviewed in Nobre et al. 2020 ).…”
Section: Converging Lines Of Evidence For Unconscious and Preconscious Perceptual Processingmentioning
confidence: 99%
“…For example, studies following Bechara et al's (1997) research on the Iowa Gambling Task found that participants often have appreciably high levels of awareness undetected by the methods employed in the original experiments (Konstantinidis & Shanks, 2014; Maia & McClelland, 2004), while a replication of Dehaene et al's (1998) subliminal semantic priming effects found a similar result (Meyen et al, 2021). In meta-analyses, we have found that awareness is reliably above chance when data are aggregated from contextual cuing (Vadillo, Konstantinidis, & Shanks, 2016) and probability cuing (Vadillo et al, 2020; see also Jiang et al, 2018) experiments almost all of which individually claim the opposite, and Nobre et al (2020) found a similar pattern in studies on implicit effects in inattentional blindness.…”
Section: Bivariate Data: the Basic Problemmentioning
confidence: 72%